Composition for reducing metal toxicity and a method thereof - Liang, Juan Boo; Jahromi, Mohammad Faseleh; Ebrahimi, Rohollah; Shokryazdan, Parisa (2014)
A composition for reducing metal toxicity, the composition comprising Lactobacillus pentosus and Lactobacillus acidipiscis in a ratio ranges from 0:1 to 1:0. A method for reducing absorption of toxic metal consumed by a subject is also provided. The method comprising administering the subject therapeutic effective amount of the composition of the present invention.